NAIL DISORDERS IN HEMODIALYSIS PATIENTS WITH CHRONIC KIDNEY DISEASE: A CROSS-SECTIONAL STUDY (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Nail disorders are common among chronic kidney disease (CKD) patients who are on maintenance hemodialysis. Even though nail abnormalities have been reported in individuals with renal impairment as well as individuals who have undergone peritoneal dialysis, there is a paucity of data that specifically discusses its prevalence in maintenance hemodialysis patients.Objectives: To identify the incidence and nature of nail disorders among patients with CKD who are on maintenance hemodialysis.Materials and Methods: It was a cross-sectional study that was carried out at the Department of Nephrology,Sir Ganga Ram Hospital, Lahore, between February 1, 2020, and August 1, 2022. The number of patients who were enrolled was 292. The clinical and laboratory diagnosis of CKD of all the patients was within two months of maintenance hemodialysis. A digital 6.0- megapixel camera was used to take nail photographs which were rated by three dermatologists independently. The diagnosis was confirmed by at least two specialists to confirm that there was a disorder. The SPSS v25.0 was used to analyze data. As a stratification factor, age, sex, and dialysis time were carried out and chi-square test was utilized; p 583Results: Out of the 292 patients, 198 (67.8) of them were male and 94 (32.2) were female with the mean age of 47.312.4years. There were 197 patients who had nail disorders (67.5%). Half-and-half nails was the most prevalent abnormality (40.8%), then splinter hemorrhages (19.2%), onycholysis (17.8%), absent lunula (16.1%), melanonychia (6.5%), chromonychia (5.5%) and Beau lines (5.1%). Abnormalities of nails had a significant relationship with both age and dialysis duration but not gender.Conclusion: Nail disorders are prevalent among patients with CKD under maintenance hemodialysis. In clinical assessment, the procedure of nail examination on a regular basis should be used as a cursory, non-invasive intervention to detect systemic complications and track the burden of disease